Measuring the accessibility of emergency shelters based on an improved two-step floating catchment area model - Yongyang Xu; Chiyu Zhou; Bin Hu (International Journal of Digital Earth)
The accessibility of emergency shelters is crucial for reducing casualties. Previous studies on the accessibility of emergency shelters have limitations in the refinement and comprehensiveness of supply and demand data. This study proposed a supply-demand optimized two-step floating catchment area method (2SFCA). The improvements consisted of three main components: refining the spatial distribution of supply and demand data, improving the travel costs based on population density, and optimizing the method for choosing emergency shelters considering the public’s willingness. Experimental results confirmed the effectiveness of the proposed method in assessing the accessibility of the population near densely distributed areas with small emergency shelters. Additionally, the proposed method outperformed traditional methods in identifying areas with low accessibility within the research area of Beijing.